Islamic Education for a Resilient Faith Communities: A Study of Religious Literacy Practices in Pesantren - Yusak, Nailil Muna; Madrah, Muna Yastuti; Ardi, Muhammad Noviani (UIN Raden Mas Said Surakarta, 2021)
This study aims to examine religious literacy practices of traditional Islamic boarding school known as Pesantren in addressing the social-religious polarization issue in Indonesia. This study employs phenomenology method with a sociology of religion approach emphasizing the religious literacy outlook. Religious literacy entails a comprehensive approach to understanding the various concept of religiosity in a plural society and adds to it the ability to critically reflect on the fundamental intersections of religion and social, political, and cultural life through multiple lenses (Moore, 2007). Data is collected through library research, field observations, structured interviews involving pesantren’s leaders, teachers and students in Pesantren Al-Muayyad, Windan, Surakarta. Discussion result shows that: 1) through a dynamic power and network mobilization, Kyai plays the role of a strategic religious actor who translates religious pluralism to the public — facilitating pesantren as community development center where authentic and meaningful socio-religious interactions among students takes place; and 2) to build a resilient faith community member, Al-Muayyad Windan designed three integrative stages of religious literacy enhancement i.e., religious literacy at the personal level, religious literacy at the intrareligious level, and religious literacy at the interreligious level.